Analysis of Critical Thinking Skills of High School Students (Jurnal Pendidikan Fisika, 2024)
Critical thinking skills are one of the essential 21st-century competencies that students must possess, as outlined by the Indonesian Ministry of Education's competency standards for graduation. The Minister of Education and Culture Decree No. 56 of 2022, which mandates the implementation of the independent curriculum, has prompted schools to change their existing curricula. This necessitates research to provide an overview of students' critical thinking skills as developed by schools. This study aims to describe the critical thinking skills of public high school students in Makassar City in the subject of Physics. The research is a quantitative descriptive survey, with the main variable being critical thinking skills, which are measured through three indicators: analysis, interpretation, and inference. The research instrument used was a six-item essay test. The population for this study consisted of all public high school students in Makassar City studying Newton's laws of motion, specifically students from SMAN 2 Makassar, SMAN 4 Makassar, SMAN 5 Makassar, SMAN 8 Makassar, and SMAN 16 Makassar. Using purposive sampling, the sample included all students from one class at each of the five schools in the population. The results indicate that 75.50% of the students' critical thinking skills in solving physics problems fall into the low category. The specific skills in analysis, interpretation, and inference are also categorized as low. Additionally, female students demonstrated a higher ratio of critical thinking skills compared to male students. In conclusion, the critical thinking skills of high school students in Makassar City remain at a low level.
Keywords: analysi; critical thinking; inference; interpretation; physics